Bio-control strategies for management of plant diseases under sustainable agriculture - Singh , Smriti; Kumawat, Kailash Chand; Kumawat, Gayatri (Indian Farming, 2024)
Over the last 15 years, microbial biological control agents (MBCAs) have seen significant research and innovation, driven by the global climate crisis and the increasing demand for food. While extensive use of chemical pesticides have caused major and oftentimes irreversible damage to the soils and thereby its productivity, these agents represent a more sustainable alternative, which not only works to eliminate pathogens but also, provides additional advantages to the soil. In this article, we discuss the mechanism of action of MBCAs, their formulations and the future they represent for agriculture.